Curriculum Dynamics and Existence of PAI: Challenges and Synergy Opportunities in Strengthening Student Character - Susetyo, Marwal Blantara; Fakhruddin, Agus; Helmy, Helmy Abdullah; Dzakiya , Mifta Ghina; Husaeni , Muhammad Fahri Ali (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
Islamic Religious Education (IRE) within the national education system faces structural challenges that are both technical-curricular and ideological-pedagogical. This study analyzes the dynamics of IRE's existence and formulates a synergistic model to strengthen student character development through a Literature Review of 13 selected articles using a Critical Content Analysis lens. Findings reveal that technical challenges include limited instructional time and overlapping values across subjects. Meanwhile, more fundamental ideological challenges stem from the epistemological dichotomy between religious and general sciences and the dominance of transmissive teaching ("banking education"). Consequently, this study proposes the Theme-Based Reciprocal Synergy Model. This model positions IRE and general subjects in a dialogical relationship through cross-subject thematic integration, pedagogical collaboration (team teaching), and holistic character assessment via portfolios. Theoretically, it strengthens the paradigm of knowledge integration, while practically providing an applicable operational framework for character education within the national curriculum by considering teacher administration policy reforms.